Isolation and Characterization of a Molybdenum-reducing and the Congo Red Dye-decolorizing Pseudomonas putida strain Neni-3 in soils from West Sumatera, Indonesia (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
The elimination of heavy metals and organic contaminants, such as phenols, hydrocarbons, and amides, by bioremediation, is the most effective choice for the foreseeable future. This is especially true at low levels, where other methods, such as physical or chemical methods, may not be successful. Each year, a few million tons of these contaminants are emitted. In this study, we examined the ability of a molybdenum-reducing bacteria that were isolated from polluted soil to decolorize azo dyes independently of its ability to reduce molybdenum. The ideal conditions for the bacterium to convert molybdate to molybdate blue are a pH range of 6.0 to 6.5 and a temperature range of 25 to 37 degrees Celsius. After glucose, fructose and galactose were the most effective donors of electrons to enable the reduction of molybdate. Galactose was the least effective supplier of electrons. There are a few other prerequisites that need to be met as well, such as a phosphate concentration of between 2.5 and 7.5 mM and a molybdate concentration of between 10 and 15 mM. Its absorption spectra were identical to that of the phosphomolybdate reduction process and to that of the earlier Mo-reducing bacterium. At a concentration of 2 ppm, the heavy metals Ag (I), Hg (II), and Cu (II) each inhibited the reduction of molybdenum by a per centage of 62.8, 61.1, and 36.8 per cent, respectively. We put the bacterium through a test to see if it can remove the color from a variety of dyes. The Congo Red dye was able to lose its color when exposed to the bacterium. Based on the results of the biochemical study, the bacterium has been provisionally identified as Pseudomonas putida strain Neni-3. This bacteria's ability to detoxify various toxicants is a desirable quality, as it makes the bacterium an efficient bioremediation approach. As a result, this bacterium is in high demand. Purification of the molybdenum-reducing enzyme that was produced by this bacterium is presently being studied in order to characterize decolorization research in a more accurate manner.
Keywords: Mo-reducing bacterium; Pseudomonas putida; Mo-blue; Azo dye-degrading; Congo red